(untitled) (International Journal of Physiotherapy, 2022)
Background: Numerous strategies and techniques are designed to treat disorders that cause body imbalance. These techniques, known as vestibular rehabilitation, focus on various exercises ranging from substitution, adaptation, habituation, and compensation. This systematic review aimed to assess the effectiveness of vestibular rehabilitation in improving balance among patients with different disorders. Material and Methods: A search of research articles in 2021 was accomplished by exploring electronic databases such as Embase, PubMed, and Scopus. Following a systematic screening and searching of articles. Fourteen relevant articles were found that were included in the review. As per the eligibility criteria, all eligible research studies were randomized controlled trials (RCTs). Results: All the included studies revealed the positive effect of vestibular rehabilitation in improving balance, and other symptoms (fatigue, vertigo, ankle sway, falls, and disequilibrium) among patients with different conditions, except one study did not find any difference between vestibular rehabilitation and standard of care. Furthermore, the reported studies indicated the benefits of the vestibular rehabilitation programs tailored to the patient’s needs and requirements compared with a single program that may not fit everyone. Conclusion: Vestibular rehabilitation protocols integrated with some technological techniques and home-based exercise programs can be considered safe and effective in improving balance among older adults suffering from different conditions affecting their balance. However, future studies with a relatively large sample size are required to assess the effectiveness of the same interventions in resource-poor settings before large-scale implementation.